Detection of DNA of Babesia canis in tissues of laboratory rodents following oral inoculation with infected ticks - Corduneanu, Alexandra; Ursache, Teodor Dan; Taulescu, Marian; Sevastre, Bogdan; Modrý, David; Mihalca, Andrei Daniel (Parasites & vectors, 2020)
BACKGROUND: Babesia spp. are apicomplexan parasites which infect a wide range of mammalian hosts. Historically, most Babesia species were described based on the assumed host specificity and morphological features of the intraerythrocytic stages. New DNA-based approaches challenge the traditional species concept and host specificity in Babesia. Using such tools, the presence of Babesia DNA was reported in non-specific mammalian hosts, including B. canis in feces and tissues of insectivorous bats, opening questions on alternative transmission routes. The aim of the present study was to evaluate if B. canis DNA can be detected in tissues of laboratory rodents following oral inoculation with infected ticks. METHODS: Seventy-five questing adult Dermacentor reticulatus ticks were longitudinally cut in two halves and pooled. Each pool consisted of halves of 5 ticks, resulting in two analogous sets. One pool set (n = 15) served for DNA extraction, while the other set (n = 15) was used for oral inoculation of experimental animals (Mus musculus, line CD-1 and Meriones unguiculatus). Blood was collected three times during the experiment (before the inoculation, at 14 days post-inoculation and at 30 days post-inoculation). All animals were euthanized 30 days post-inoculation. At necropsy, half of the heart, lung, liver, spleen and kidneys were collected from each animal. The presence of Babesia DNA targeting the 18S rRNA gene was evaluated from blood and tissues samples. For histopathology, the other halves of the tissues were used. Stained blood smears were used for the light microscopy detection of Babesia. RESULTS: From the 15 pools of D. reticulatus used for the oral inoculation, six were PCR-positive for B. canis. DNA of B. canis was detected in blood and tissues of 33.3% of the animals (4 out of 12) inoculated with a B. canis-positive pool. No Babesia DNA was detected in the other 18 animals which received B. canis-negative tick pools. No Babesia was detected during the histological examination and all blood smears were microscopically negative. CONCLUSIONS: Our findings demonstrate that B. canis DNA can be detected in tissues of mammalian hosts following ingestion of infected ticks and opens the question of alternative transmission routes for piroplasms.
Keywords: Animals; Gerbillinae; babezióza; RNA, Ribosomal, 18S; Female; Gerbil; infestace klíšťaty; ženské pohlaví; Rodentia; Oral inoculation; Mouse; Mice; Dermacentor; Babesia canis; myši; Dermacentor reticulatus; Babesiosis; DNA, Protozoan; Male; protozoální DNA; aplikace orální; RNA ribozomální 18S; Babesia; hlodavci; Administration, Oral; zvířata; mužské pohlaví; Tick Infestations